Youth violence and the brain : exposure to violence and deactivation of an insular-frontal network of cortical areas associated with inhibitory control - Car?, Valentina Metsavaht (2018)
This study investigates the effects of preadolescent exposure to violence on brain function using functional magnetic resonance imaging (fMRI) and a task that tests executive functions. Executive functions are impaired in different disorders, and also as a result of adverse life conditions such as stress and abuse. Based on the literature, we hypothesized that exposure to violence would impact executive functions and their neurobiological correlates. The task performed during fMRI was a sustainned attetion task that tests for inhibitory control. Exposure to violence and behavior were investigated using self-reports (Juvenile Victimization Questionnaire and the Childhood Behavior Checklist). In total, 42 preadolescents (ages 10-14), recruited from public schools in one of the most violent cities in the world participated in the study. Results showed a significant negative correlation between the scores for exposure to violence and brain funtion in a fronto-parietal-insular network: preadolescents with higher levels of exposure to violence showed deactivation of bilateral insula and superior frontal cortex. These brain areas are associated with attention and inhibitory control. The findings provide evidence that preadolescent victimization and exposure to violence alters the neural patterns underlying executive functioning, and suggest that executive function tranining may be a candidate for targeted interventions in preadolescents exposed to violence.